ESTUDIOS SOBRE HEMATOZOARIOS I PLASMODIUM MEXICANUM THOMPSON AND HUFF 1944 EN SUE HUESPEDES NATURALES - PEREZ REYES, R; PELAEZ, DIONISIO; BARRERA, ALFREDO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
The results obtained in a study of the incidence of pectin-fermenting strains among 154 strains of coliform bacteria isolated from 20 milk samples indicated that only 3 fermented pectin and were classified as Escherichia coli intermediates [Probably shou
AN ESC NAC CIENC BIOL
Keywords: ESTUDIOS, HEMATOZOARIOS, PLASMODIUM, MEXICANUM, NATURALES; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); PARASITOLOGIA ANIMAL